Phylogenetic clustering among aggressive competitors: evidence from odonate assemblages along a riverine gradient - Saito, Victor S.; Valente-Neto, Francisco; Rodrigues, Marciel Elio; de Oliveira Roque, Fabio; Siqueira, Tadeu [UNESP] (Springer Nature, 2016)
Studies on phylogenetic community ecology usually infer habitat filtering when communities are phylogenetically clustered or competitive exclusion when communities are overdispersed. This logic is based on strong competition and niche similarity among closely related species—a less common phenomenon than previously expected. Dragonflies and damselflies are good models for testing predictions based on this logic because they behave aggressively towards related species due to mistaken identification of conspecifics. This behavior may drive communities toward phylogenetic overdispersion if closely related species frequently exclude each other. However, phylogenetically clustered communities could also be observed if habitat filtering and/or competitive asymmetry among distantly related species are major drivers of community assembling. We investigated the phylogenetic structure of odonate assemblages in central Brazil in a watershed characterized by variations in stream width, vegetation cover, aquatic vegetation, and luminosity. We observed general clustering in communities according to two indices of phylogenetic structure. Phylogenetic beta diversity coupled with Mantel tests and RLQ analysis evidenced a correlation between the riverine gradient and phylogenetic structure. Larger rivers with aquatic vegetation were characterized by anisopterans, while most zygopterans stayed in small and shaded streams. These results indicate niche conservatism in Odonata habitat occupancy, and that the environment is a major influence on the phylogenetic structure of these communities. We suggest that this is due to clade-specific ecophysiological requirements, and because closely related species may also have competitive advantages and dominate certain preferred habitats.
Keywords: Community assembly; Damselfly; Dragonfly; Ecophylogenetic; Ecophysiological hypothesis